Responsibility of the National Land Agency Regarding Overlapping Land Ownership Certificates (A Study at the Malang City Land Office) - Muhamad Irwan Sugianto; Budi parmono; Sunardi Sunardi (Eduvest - Journal of Universal Studies, 2025)
This study examines the responsibilities of the National Land Agency (BPN) regarding overlapping land ownership certificates at the Malang City Land Office. Land is a fundamental need, leading to conflicts over ownership and use. Legal certainty in land rights is essential and is mandated by the Basic Agrarian Law (UUPA) and Government Regulation No. 24 of 1997. However, overlapping certificates often arise due to factors such as bad faith among applicants, lack of awareness among landowners, and errors by land office officials. This research employs empirical legal research methods, using interviews and documentation to analyze the causes and responsibilities of the Malang City Land Office in managing land certificate overlaps. The findings indicate that the office must improve its verification processes and community engagement to prevent future disputes.